Curdlan Prevents the Cognitive Deficits Induced by a High-Fat Diet in Mice via the Gut-Brain Axis - Yang, Xiaoying; Zheng, Mingxuan; Hao, Shanshan; Shi, Hongli; Lin, Danhong; Chen, Xi; Becvarovski, Alec; Pan, Wei; Zhang, Peng; Hu, Minmin; Huang, Xu-Feng; Zheng, Kuiyang; et al. (Frontiers in Neuroscience, 2020)
A high fat (HF) diet is a major predisposing factor of neuroinflammation and cognitive deficits. Recently, changes in the gut microbiota have been associated with neuroinflammation and cognitive impairment, through the gut-brain axis. Curdlan, a polysaccharide widely used as food additive, has the potential to alter the composition of the microbiota and improve the gut-brain-axis. However, the effects of curdlan against HF diet-induced neuroinflamamtion and cognitive decline have not been investigated. We aimed to evaluate the neuroprotective effect and mechanism of dietary curdlan supplementation against the obesity-associated cognitive decline observed in mice fed a HF diet. C57Bl/6J male mice were fed with either a control, HF or HF with curdlan supplementation diets for 7 days (acute) or 15 weeks (chronic). We found that acute curdlan supplementation prevented the gut microbial composition shift induced by HF diet. Chronic curdlan supplementation prevented cognitive declines induced by HF diet. In addition, curdlan protected against the HF diet induced abnormities in colonic permeability, hyperendotoxemia and colonic inflammation. Furthermore, in the prefrontal cortex and hippocampus, curdlan mitigated microgliosis, neuroinflammation and synaptic impairments induced by a HF diet. Thus, curdlan – as food additive and prebiotic – can prevent cognitive deficits induced by HF diet via the microbiota-colon-brain axis.